2014
DOI: 10.1093/humrep/deu033
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between standard blastocyst morphology, euploidy and implantation: an observational study in two centers involving 956 screened blastocysts

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
282
7
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 428 publications
(317 citation statements)
references
References 34 publications
22
282
7
6
Order By: Relevance
“…The difference in findings between studies may be attributable to the later day of biopsy in our study (Day 5) compared to theirs (Day 3), or the lower overall aneuploidy rate among day 5 blastocysts in our study. These findings are similar to a recent morphokinetic study that observed a delay in the initial compaction and blastulation among aneuploid embryos relative to euploid counterparts [12] but contrasts with a retrospective multicenter analysis that did not observe any significant difference in euploid or implantation rates between day 5 or day 6 blastocysts [7] and another morphokinetic study that did not find any correlation between aneuploid rates and the timing of initiation or completion of blastulation [13]. Due to the inconsistency of study results, a larger analysis with a diverse patient population and uniformity of chromosomal analysis is obviously needed.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The difference in findings between studies may be attributable to the later day of biopsy in our study (Day 5) compared to theirs (Day 3), or the lower overall aneuploidy rate among day 5 blastocysts in our study. These findings are similar to a recent morphokinetic study that observed a delay in the initial compaction and blastulation among aneuploid embryos relative to euploid counterparts [12] but contrasts with a retrospective multicenter analysis that did not observe any significant difference in euploid or implantation rates between day 5 or day 6 blastocysts [7] and another morphokinetic study that did not find any correlation between aneuploid rates and the timing of initiation or completion of blastulation [13]. Due to the inconsistency of study results, a larger analysis with a diverse patient population and uniformity of chromosomal analysis is obviously needed.…”
Section: Discussionsupporting
confidence: 84%
“…Many centers do not biopsy day 5 morulae or early blastocysts, limiting day 5 biopsy to only expanded or expanding blastocysts, and choosing to rather wait until day 6 to determine if subsequent development warrants day 6 biopsy and immediate cryopreservation of embryos that have not reached the expanded blastocyst stage on day 5 [7]. However, these slower but non-arrested embryos are frequently found to have progressed to blastocyst stage by the time of a day 6 transfer, and the inability to perform a day 5 biopsy on these embryos precludes the availability of genetic information by the time of a fresh day 6 transfer.…”
Section: Introductionmentioning
confidence: 99%
“…The biopsy procedure was performed as previously described. 19 5-10 TE cells were aspirated into the TE biopsy pipette (Research Instruments) followed by laser-assisted removal of the target cells from the body of the embryo. TE rebiopsies on aneuploid embryos were carried out following the same protocols used for TE biopsies during clinical PGS cycles.…”
Section: Ivf Proceduresmentioning
confidence: 99%
“…The quality of the blastocyst has been associated with the results of comprehensive chromosome screening of trophectoderm biopsies [10].…”
Section: Discussionmentioning
confidence: 99%